Asn12 and Asn278: Critical Residues for In Vitro Biological Activity of Reteplase - Naganath Mandi; Kalyana R. Sundaram; Sunil K. Tandra; Suman Bandyopadhyay; Sriram Padmanabhan (Advances in Hematology)
Reteplase (rPA) is a thrombolytic agent used for the treatment of acute myocardial infarction. We studied the expression of rPA and its selected asparagine mutants after integration into the Pichia genome. Though methanol induction of the native and the rPA mutants showed similar expression levels (~200–250 mg/L), the mutants displayed significant loss of protease activity. Strikingly, the clot lysis activities of these mutants were considerably different. While mutation of Asn12 (N12P) of the Kringle 2 domain showed delayed clot lysis activity (𝑡1/2=38 min) compared to the native rPA (𝑡1/2=33 min), a faster rate of clot lysis (𝑡1/2=27 min) was observed when the Asn278 (N278S) of the serine protease domain was mutated. Interestingly, the slowest clot lysis activity (𝑡1/2=49 min) demonstrated by the double mutant (N12P, N278S) suggests the dominant role of Asn12 in regulating the fibrinolytic activity of rPA. The results presented in this paper indicate that the fibrinolytic and the proteolytic activities of rPA are independent of each other.